The Application of Herbal Medicines for Parasites Control in Aquaculture: A Review - Xiaoping Tan; Chengzhong Yang; Qianwen Zhou; Shenye Qu; Tianqiang Liu; Fei Ling; Gaoxue Wang (Reviews in Aquaculture, 2026)
With the ongoing expansion of intensive aquaculture, the emergence of parasite drug resistance and the increasing frequency of disease outbreaks have become significant challenges. Conventional antiparasitic agents are increasingly restricted due to burgeoning resistance, environmental persistence, and safety concerns. Consequently, the development of eco‐friendly and sustainable therapeutic alternatives has emerged as a primary research priority. Herbal medicines (HMs), characterized by a vast reservoir of structurally diverse and bioactive compounds, serve as ideal candidates for drug discovery in aquaculture. In recent years, substantial research effort has been directed toward identifying commercially viable HM‐derived agents for the fish farming industry. Advancements in isolation and purification technologies have facilitated the extraction of numerous insecticidal small molecules, while further studies have elucidated their underlying antiparasitic mechanisms. This review provides a comprehensive analysis of the role of HMs in preventing and treating aquatic parasitic infections, encompassing the isolation of active constituents, evaluation of efficacy, modes of action, and optimization of application strategies. Furthermore, we address the inherent challenges and future trajectories of utilizing HMs in aquaculture. By synthesizing current knowledge on these bioactive compounds, this review aims to facilitate the development of safe, highly bioavailable, and environmentally sustainable antiparasitic agents.